VISIBLE AND INFRARED TELESCOPES IN DETECTION OF EARTH-LIKE EXOPLANETS - Yegorov, A. D.; Yegorov, V. A.; Yegorov, S. A.; Yelenskaya, L. I.; Sinel’nikov, I. Ye. (Видавничий дім «Академперіодика», 2016)
PACS number: 95.55.FwObject and purpose: The study examines the balance of resolving and light-harvesting (penetrating) abilities of filled and sparse aperture telescopes in direct detection of terrestrial exoplanets. We assess the role of quantum fluctuations of luminous flux in optical and infrared bands. Studied are the ways to deal with diffraction spreading of sparse aperture under conditions of high luminosity contrast between a star and a planet.Methods and methodology: Resolution problem is considered in the Fraunhofer approximation. In the one-dimensional version, we present the method of synthesis of an apodizing function of a sparse aperture telescope by means of the “hill climbing” algorithm. We also investigate the effectiveness of a recursive approach in forming an apodizing function for the partial subapertures.Findings: Our study offers estimations of the maximum range in the direct detection of terrestrial exoplanets, which were obtained through observations in visible and infrared bands, and its dependence on wavelength and aperture size. They indicate the lack of balance in the light-harvesting and resolving abilities of telescopes with filled aperture in different spectral bands, taking into account the quantum fluctuations of luminous flux. The proposed solution is to implement a balanced resolving and lightcollecting ability of telescopes with sparse aperture. Optical schemes which allow to eliminate chromatic effect during interferometric observations in survey mode are suggested.Conclusions: Switch-over to the infrared range while using sparse aperture improves the balance and reduces the contrast of the central star and the planet. To reduce the diffraction spreading of a telescope with sparse aperture we offer apodization with a recursive use of the binomial coefficients not only for the lens as a whole but for the partial sub-apertures as well. The advantages of a long-focus and low optical power scheme are also specified.Key words: exoplanets, balance of resolving and light-harvesting abilities of telescopes, apodizing functionManuscript submitted 20.09.2015Radio phys. radio astron. 2016, 21(1): 14-23 REFERENCES1. ARMSTRONG, S. and SANDBERG, A., 2013. Eternity in six hours: Intergalactic spreading of intelligent life and sharpening the Fermi paradox. Acta Astronaut. vol. 89, pp. 1–13. DOI: https://doi.org/10.1016/j.actaastro.2013.04.002 2. FRANCIS, T. S. Yu., 1973. Introduction to Diffraction, Information Processing, and Holography. Cambridge, Mass.: The MIT Press 3. KRAUS, J. D., 1966. Radioastronomy. New York: MakGrau-Hill. 4. CHRISTIANSEN, W. W. and HOGBOM, J. A., 1969. Radioteleskopes. Cambridge: CambridgeUniversity Press. 5. MOORE, P. and REES, R., eds. 2011. Patrick Moore's Data Book of Astronomy. Cambridge:CambridgeUniversity Press. 6. KUCHNER, M. J. and TRAUB, W. A., 2002. Acoronograph with a band-limited mask for finding terrestrial planets. Astrophys. J. vol. 570, no. 2, pp. 900–908. DOI: https://doi.org/10.1086/339625 7. WATSON, S. M., MILLS, J. P., GAISER, S. L. and DINER, D. J., 1991. Direct imaging of nonsolar planets with infrared telescopes using apodised coronograps. Appl. Opt. vol. 30, no 22, pp. 3253–3262. DOI: https://doi.org/10.1364/AO.30.003253 8. GUYON, O., PLUZHNIK, E. A., KUCHNER, M. J., COLLINS, B. and RIDGWAY, S. T., 2006. Theoretical Limits on Extrasolar Terrestrial Planet Detection with Coronagraphs. Astrophys. J. Supp. Ser. vol. 167, no. 1, pp. 81–99. DOI: https://doi.org/10.1086/507630 9. SODIN, L. G., 2005. Some Problems of the Phased Array Theory Relevant in Radio Astronomy. Radio Phys. Radio Astron. vol. 10, special is., pp. 128–142 (in Russian). 10. KRAUS, J. D., 2001. Antennas. New Delhi: Tata McGraw-Hill Publishing Co. Ltd. 11. 1980. Adaptive optics, collected writings.Moscow: Mir Publ. (in Russian). 12. VASIL'EV, F. P., 1980. Numerical methods for solving extreme problems. Moscow: Nauka Publ. (in Russian). 13. THOMPSON, B. J. and SHANNON, R. R., eds. 1974. Space Optics: Proceedins of the ninth international congress of the international commission for optics (ico IX). Washington, D.C.: National Academies of Sciences.